Acute Lymphoblastic Leukemia in the Course of Polycythemia Vera: A Case Report and Review of Literature - Wu, Dijiong (Indian J Hematol Blood Transfus, 2015)
INTRODUCTION: Polycythemia vera (PV) is one of the most common forms of myeloproliferative neoplasms. Acute myeloid leukemia secondary to PV is well reported, and the mechanism has been clarified to some extent. Only a limited number of cases have been reported about the development of acute lymphoblastic leukemia (ALL) in the course of PV, and the possible underlying mechanism has not been explored well. CASE PRESENTATION: A 75-year-old patient who developed ALL 3 years after he was diagnosed with PV. The presence of remarkable splenomegaly, typical immunophenotyping of the peripheral blood and increased expression of serum fibrosis markers indicated the existence of extramedullary hematopoiesis which may ascribe to myelofibrosis. After the treatment of dosage-modulated chemotherapy, the patient got complete remission. CONCLUSION: The JAK2 mutation may the underlying factor that contributes to the development of ALL, and the existence of MF may indicate the progression to post- polycythemic MF, which may be a risk factor for the accelerated transformation.